Performance studies of MRPC prototypes for CBM - Deppner, Ingo Martin; Herrmann, Norbert; Frühauf, J.; Kiš, M.; Lyu, P.; Loizeau, P.-A.; Shi, L.; Simon, Christian; Wang, Y.; Xie, B. (Journal of Instrumentation, 2016)
Multi-gap Resistive Plate Chambers (MRPCs) [1] with multi-strip readout are considered to be the optimal detector candidate for the Time-of-Flight (ToF) wall in the Compressed Baryonic Matter (CBM) experiment. In the R&D phase MRPCs with different granularities, low-resistive materials and high voltage stack configurations were developed and tested. Here, we focus on two prototypes called HD-P2 and THU-strip, both with strips of 27 cm length and low-resistive glass electrodes. The HD-P2 prototype has a single-stack configuration with 8 gaps while the THU-strip prototype is constructed in a double-stack configuration with 2 × 4 gaps. The performance results of these counters in terms of efficiency and time resolution carried out in a test beam time with heavy-ion beam at GSI in 2014 are presented in this proceeding even though the incident particle flux of a few hundred Hz/cm2 does not meet the real CBM conditions (between 1.5 kHz/cm2 and 10 kHz/cm2 for these counters).
Gesehen am 07.05.2020